Malaysia commitment towards low carbon cities - Abdul Rahman, Haliza (Human Resource Management Academic Research Society, 2020)
Introduction: Low Carbon City (LCC) is a city that comprises of societies that consume sustainable green technology, green practices and emit relatively low carbon or Green House Gases (GHG). Objective: The overall objective of a LCC is to significantly reduce its carbon footprint in ways that do not compromise a city’s economic development potential. Method: Secondary data are collected with regard to “low carbon cities” scope matters. Result. The carbon dioxide (CO2) emission in 2008 was an estimated 2,347,538 tonnes and this is expected increase up to 11,689,308 tonnes by 2020. Hence, Malaysia’s leaders have made ambitious commitments to reduce the carbon and energy intensity of the economy and transition to a low-carbon growth path. In 2009, Malaysia in COP15 at Copenhagen, Denmark, proposed to reduce CO2 emission intensity in Malaysia to 40 per cent by the year 2020 compared with its 2005 levels. Since that, Malaysian Government actively advocates and promotes green and low carbon development especially in the city. The Low Carbon Cities Framework (LCCF) was initiated to provide a framework to achieve sustainable developments that will subsequently reduce carbon emissions. The progress of LCC initiatives is through the years with phase by phase, and city by city. Conclusion: To meet national ambition to be as many as a carbon-free cites in Malaysia, its needs a strong and effective coordination between international, national, regional and local institutions, integration into different sectoral priorities and policies, and engagement between the public, private and civic sectors as well.